IMPORTANCE OF SPIRITUAL WORLDVIEW FOR FUTURE TEACHERS - Paridinova Botagoz; Kaldybay Kainar (Scientific Journal of Pedagogy and Economics, 2020)
The importance of a spiritual worldview for future teachers was relevant at all stages of the development of society. All the qualities that characterize the spiritual worldview of teachers are changed, depending on the social structure of the state and its ideology, religious and secular views, and the level of development of pedagogical science. The spiritual worldview of teachers is one of the most important characteristics of the pedagogical preparation of the individual. The formation and development of the spiritual worldview, is interconnected from the moral choice of the ideal of good and humanistic point of view. The work discusses the pedagogical problems of the spiritual worldview of future teachers. The article defines the concept of “Spiritual worldview”. The aim of this work is to generalize and systematize the problem, to determine the role and place of the spiritual worldview of future teachers. This study discusses some of the findings of scientists on the worldview and spirituality in education to achieve the goal. There were discussed the fundamental principles of development and the existing scientific work on the problem of the spiritual worldview. The presented characteristic of important aspects of the spiritual worldview of future teachers for universities, future teachers, schools and students. It is argued that a deep study of the spiritual worldview will make the importance clear for future teachers. The methodological basis of the study is the scientific works of domestic, Russian and foreign researchers, their main provisions for the study of spirituality and worldview. In the work are used the methods of system analysis, comparison of foreign, domestic and Russian works on the problem of the spiritual worldview of future teachers in modern society.